2007
DOI: 10.1108/09654280710731566
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviours and reproductive health knowledge among in‐school young people with disabilities in Ibadan, Nigeria

Abstract: PurposeThe paper seeks to explore sexual behaviours and reproductive health knowledge among in‐school young people with disabilities (PWD) in Ibadan, Nigeria.Design/methodology/approachIn the paper a structured questionnaire was administered to 103 randomly selected PWD, aged ten to 25, from four integrated secondary schools in Ibadan. The data were collected through face‐to‐face interview. Five categories of disability included were hearing and speech, sight, speech, intellectual, and physical disabilities.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…This indicates an urgent need to develop interventions tailored to the specific needs of this group of adolescents. Similar results were reported by other researchers (McGillivray 1999, Dawood et al 2006, Olaleye et al 2007). On the contrary, Gilbert (2007) reported a high level of HIV knowledge in a sample of learners with intellectual impairments with prior exposure to HIV education, showing that HIV-prevention education in appropriate format can increase HIV knowledge of this category of learners.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates an urgent need to develop interventions tailored to the specific needs of this group of adolescents. Similar results were reported by other researchers (McGillivray 1999, Dawood et al 2006, Olaleye et al 2007). On the contrary, Gilbert (2007) reported a high level of HIV knowledge in a sample of learners with intellectual impairments with prior exposure to HIV education, showing that HIV-prevention education in appropriate format can increase HIV knowledge of this category of learners.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, stakeholders such as teachers, parents, caregivers, and HIV experts or health workers often lack skills and tools to pass on HIV-prevention education in accessible formats to individuals with intellectual impairments (Olaleye et al 2007, Rohleder and Swartz 2009, Rohleder et al 2012. Apart from advocating the development and inclusion of tailored HIV-prevention and sexuality education interventions in the school curriculum, parents, caregivers, teachers and communities should participate and/or collaborate in such endeavours (Birch, Angermeier andGentsch 2002, Brown andJemmott 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Previous research findings indicate that persons with disabilities access HIV and sexual and reproductive health (SRH) information from a range of sources but mostly from radio, television and health professionals [15–17]. However, available evidence suggests less access to HIV/SRH information and services and more risky sexual practices among persons with intellectual disabilities than other persons with disabilities [15,18]. There are documentations of inadequate HIV transmission and prevention knowledge, as well as risky sexual behaviours among persons with different impairments, with female tending towards lower HIV knowledge than male [15,16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study [18] explored sexual behaviours and reproductive health knowledge of in-school young persons with hearing, visual, speech, intellectual and physical disabilities in Ibadan, Nigeria (only 10 of the 103 participants had intellectual impairments). They found that 35% of their participants were sexually experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with people with disabilities or staff and key informants report relatively high rates of unsafe sex and other risk behaviours including substance use, transactional sex, and reported incidence of previous sexually transmitted diseases (Blanchett, 2000;Brown et al, 1997;Cambridge, 1996;Carey et al, 1997;Carey et al, 1999;Carey et al, 2001;Carey et al, 2004a;Chandra et al, 2003;Choquet et al, 1997;Chopra et al, 1998;Chuang & Atkinson, 1996;Collins et al, 2008a;Collins et al, 2008b;Davidson et al, 2001;Devieux et al, 2007;Gordon et al, 1999;Grassi et al, 1999a;Grassi et al, 1999b;Kalichman et al, 1994;Katz et al, 1994;Kelly et al, 1992; M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 1995; Maart & Jelsma, 2010;Meade & Sikkema, 2007;Meade & Sikkema, 2005;Menon & Pomerantz, 1997;Menon et al, 1994;Myer et al, 2009;Ogunsemi et al, 2006;Olaleye et al, 2007;Otto-Salaj et al, 1998;Randolph et al, 2009;Rohleder, 2010;Smit et al, 2006;Susser et al, 1995;Thompson, 1994;Touko et al, 2010;Vanable et al, 2007;Weinhardt et al, 1998;Walkup et al, 1999).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%